Study on Rheological Mechanism of Cement-Coal Gangue Cementitious Material (CGCM) Slurry. (13th April 2022) - Shi, Xuyang; Cai, Qingxiang; Zhang, Linglei; Chen, Yanlong; Li, Ming
Abstract : To explore the rheological mechanism of cement-coal gangue cementitious material (CGCM) slurry, the effects of the activation temperature (500°C-900°C) of coal gangue on the initial fluidity, plastic viscosity ( η0 ), and yield stress ( τ0 ) of CGCM slurry were considered, the variation laws of rheological parameters of CGCM slurry at different hydration ages were compared, and the rheological equations of CGCM slurry were established in this study. The results show that the rheological law of the CGCM slurry conforms to the modified Bingham model, and the significant shear thinning occurs in the CGCM slurry at low-shear speed, and relatively weak shear thickening occurs in the CGCM slurry at high-shear speed; under the thermal activation temperature of 800°C, the pozzolanic activity of coal gangue reaches the highest, the hydration reaction is the fastest, and the initial fluidity of CGCM slurry at 800°C is the lowest; the plastic viscosity of CGCM slurry increases gradually with the increase of thermal activation temperature of coal gangue, and the yield stress of the CGCM slurry reaches the maximum at 800°C; the flow law of CGCM slurry has significant time-varying characteristics, and the plastic viscosity and yield stress of CGCM slurry increase gradually with the extension of hydration time. This study shows that the fluidity of coal gangue cement slurry has significant time-varying characteristics, which can provide effective theoretical support for the accurate application of coal gangue cement in grouting engineering.